Judgments of the Court of Appeal of New Zealand on Proceedings to Review Aspects of the Report of the Royal Commission of Inquiry into the Mount Erebus Aircraft Disaster : C.A. 95/81 - New Zealand. Court of Appeal (Salt Lake City, UT : Project Gutenberg, 2005)
"Judgments of the Court of Appeal of New Zealand on Proceedings to Review Aspects of the Report of the Royal Commission of Inquiry into the Mount Erebus Aircraft Disaster" is a legal document detailing the judicial review of findings related to a significant aviation disaster that occurred in the late 20th century. This work pertains to a courtroom judgment, showcasing legal arguments surrounding the investigation's findings and the reputations of prominent individuals in Air New Zealand following the tragedy, which resulted in the loss of 257 lives. The opening of the text sets the stage for a legal examination of a report that criticized Air New Zealand senior officers following an aircraft disaster involving their DC-10. The proceedings focus on challenging certain findings in that report, particularly allegations of a conspiracy and acts of deception alleged against the airline's management. It establishes that the court will explore the jurisdiction of the Commission and natural justice principles, highlighting the grave implications such findings might have on reputations and potential legal repercussions, thus framing the legal discourse that follows. (This is an automatically generated summary.)
Release date is 2005-06-25
E-text prepared by Jonathan Ah Kit, Ralph Janke, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Air New Zealand; New Zealand. Royal Commission to Inquire into the Crash on Mount Erebus, Antarctica, of a DC10 Aircraft Operated by Air New Zealand Limited; Aircraft accidents